DIFFICULTIES OF DIAGNOSTICS OF ENTEROVIRUS INFECTION IN INFANT AND CLINICAL-MORPHOLOGIC COMPARISONS - D. Yu. Ovsyannikov; L. V. Pushko; J. I. Kuznetsova; M. G. Kantemirova; O. I. Soboeva; T. Yu. Illarionova; A. B. Bogdanov; G. M. Drogova; I. E. Koltunov (LLC "Diagnostics and Vaccines", 2015)
This paper describes a clinical case of intrauterine generalized enterovirus infection in infant 2 months with fatal outcome. Hematologic features (lymphocytic leikemoid reaction), difficulties of diagnostics and treatment, results of autopsy are presents.